“Topos e dramaturgia” - Marta Grabocz; (Traducción) Alberto Leongomez Herrera (Pensamiento Palabra y Obra, 2013)
“Topoi and dramaturgy”: analysis of the meanings and the expressive strategy in two symphonic movements of Bela